Post-Heteronormativität und Schule Soziale Deutungsmuster von Lehrkräften über vielfältige geschlechtliche und sexuelle Lebensweisen - Klenk, Florian Cristobal (Studien zu Differenz, Bildung und Kultur, 2023)
Gender and sexual diversity is becoming a topic in everyday school life, but still occupies a precarious position in it - this not only affects LGBTIQ* children and young people, but also educational professionals, as this study shows. Based on a critically deconstructive pedagogy and on qualitative interviews with lesbian, gay, bi- and heterosexual as well as inter*, trans* and cisgender teachers, the study reconstructs social patterns of interpretation about how they deal with and address diverse lifestyles at school and in the classroom. The study makes an innovative contribution to an area of educational science that has hardly been researched so far and thus provides new impulses for a queer professionalisation of (future) teachers.